Synthesis, characterization, OFET, and DFT study of the novel ball-type metallophthalocyanines bridged with four diaminopyrimidine-dithiol - Molla, Fadime; Yazici, Aysegul; Acar-Selcuki, Nursel; Altindal, Ahmet; Salih, Bekir; Bekaroglu, Ozer (World Scientific Publ Co Pte Ltd, 2020)
Co2Pc2 (2) and Zn2Pc2 (3) were obtained in DMF and LuPc2 (4) was obtained in hexanol by the cyclotetramerization of novel diphthalonitrile (1). Synthesized compounds were characterized by FT-IR, H-1-NMR, elemental analyses, MALDI-TOF MS and UV-vis spectroscopy techniques. Optimized geometries and electronic structures for compounds 2, 3 and 4 were investigated by Density Functional Theory (DFT) and Time Dependent Density Functional Theory (TD-DFT). In compound 2, a new bond was observed between Co centers forming two Co(III) with the interaction of d orbitals. Computational and experimental UV-vis spectra in DMF were found in agreement for the investigated compounds. Vertical and adiabatic ionization potentials for the studied systems were also calculated. The gate dielectric performances of thin films obtained from these compounds were investigated by fabricating ITO/2-4/Au devices. The observed reverse bias J-V characteristics revealed that the leakage current in ITO/2-4/Au devices is because of the Poole-Frenkel effect. The effect of the gate dielectric on the OFET performance parameters was also investigated by fabricating bottom-gate top-contact OFET using pentacene as the active layer. Maximum field effect mobility was observed with the 2-based OFET device. Calculated HOMO-LUMO gap, hole reorganization energy and ionization energy have also supported the experimental results which indicate that 2 is the most suitable system for OFET devices.
Keywords: ball-type phthalocyanines; homodinuclear; leakage current; density functional theory; OFET